Eksplorasi Geometri Proyektif dan Teori Rumah Sederhana pada Museum Saoraja Mallangga - Jafaruddin; Reski, Sri; Aemiliana, Aemiliana; Fasira, Erra; Nurhaita, Nurhaita; Mutmainnah, Nur Inayah; Ibrahim, Andi Achmad (Issues in Mathematics Education (IMED), 2024)
Mathematics is an important part of education. Mathematics not only plays an important role in the realm of formal education, but also has a close connection with the culture around us. The aim of this research is to determine projective geometry in the form of building numbers and projective coordinates of the saoraja mallangga museum, which is located in kec. tempe, kab. wajo, south sulawesi. The research method used is qualitative research with an ethnographic approach, where data is collected through interviews, documentation and observation. The results of the research show that the building numbering and house diagrams at the saoraja mallangga museum obtained projective coordinates of . It is hoped that this research can improve students direct understanding of mathematical concepts through learning resources at cultural sites, especially at the simettengpola saoraja museum mallangga.